Molecular electrostatic potential, HOMO-LUMO and vibrational study of aristolochic acid II using density functional theory - Khadka, Jang Bahadur; Joshi, Bhawani Datt (BIBECHANA, 2014)
Because of their wide applications in human or animal medicine, the natural products have been the subject of investigation. Aristolochic acids (AAs) (Aristolochiaceae), however toxic, are reported for many medicinal uses. In this work, computational study on the molecular properties of AA II is presented using density functional theory (DFT), B3LYP functional along with Hartree-Fock (HF) theory at 6-311++G(d,p) level. A complete vibrational assignment has been done for the observed FT-IR and Raman wavenumbers with the results of quantum chemical calculations. The structure–activity relationship has been interpreted by mapping electrostatic potential surface (MEP). Graphical representation of frontier molecular orbitals with their energy gap has been analyzed theoretically for both the gaseous and solvent environment employing TD-DFT using IEF-PCM model. DOI: http://dx.doi.org/10.3126/bibechana.v12i0.11702 BIBECHANA 12 (2015) 40-52